2010
DOI: 10.1021/cm1006108
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Template Structure and Synergism between Inorganic and Organic Structure Directing Agents in the Synthesis of UTL Zeolite

Abstract: The extra-large-pore germanosilicates with UTL topology have been synthesized using a large variety of spiroazocompounds as structure-directing agents. Synthesis conditions were optimized and zeolites with a high crystallinity degree were obtained with 13 different organic structure-directing agents. The influence of the composition of the reaction mixture and template nature (structure, hydrophilicity/hydrophobicity balance, rigidity, pK a) on the phase selectivity, crystallinity degree, and adsorption proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 60 publications
6
84
1
Order By: Relevance
“…[25] The reaction gel was prepared as followed: template (6R,10S)-6,10-dimethyl-5-azoniaspiro [4.5]decane (67.83 g) was dissolved in water (500 g) and the template was ion-exchanged into HO À form using AG 1-X8 resin (Bio-Rad). Then, GeO 2 (38.76 g) was dissolved in the solution of template and SiO 2 (Cab-O-Sil M5, 44.5 g) was added.…”
Section: Methodsmentioning
confidence: 99%
“…[25] The reaction gel was prepared as followed: template (6R,10S)-6,10-dimethyl-5-azoniaspiro [4.5]decane (67.83 g) was dissolved in water (500 g) and the template was ion-exchanged into HO À form using AG 1-X8 resin (Bio-Rad). Then, GeO 2 (38.76 g) was dissolved in the solution of template and SiO 2 (Cab-O-Sil M5, 44.5 g) was added.…”
Section: Methodsmentioning
confidence: 99%
“…The molar composition of the reaction gel for all UTL was Si/Ge = 2 [33,34], for Al-UTL Si/Ge = 2, (Si + Ge)/Al = 96 [35], for B-UTL in 3b Si/Ge = 1.7, (Si + Ge)/B = 9, in 4a Si/Ge = 1.2 and (Si + Ge)/B = 6.7, and in 4b Si/Ge = 1.9 and (Si + Ge)/B = 32) [35,36].…”
Section: Preparation Of Zeolite Utlmentioning
confidence: 99%
“…[16][17][18][19] Recently, much progress has been made to design distinctive organic templates, among which diquaternary ammonium is a kind of important templates with good exibility and feasibility. [20][21][22][23][24][25][26] Its end groups and chain length can be selectively altered to facilitate the formation of diverse microporous topology, and even sometimes to tailor the crystal morphology or mesoporosity. Thereinto, Moini et al investigated the directing role of (CH 3 ) 3 N + (CH 2 ) n N + (CH 3 ) 3 by regulating (CH 2 ) n length, in which they found that EUO zeolite can be produced with n ¼ 5, 6, NEI zeolite with n ¼ 10, MTT zeolite with n ¼ 7, 8, 9, 11, 12, and MTW with n ¼ 9, 14.…”
Section: Introductionmentioning
confidence: 99%